Efficacy and safety of novel carbapenem–β-lactamase inhibitor combinations: Results from phase II and III trials - Yu, Wei; Shen, Ping; Luo, Qixia; Xiong, Luying; Xiao, Yonghong (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives The addition of novel β-lactamase inhibitors to carbapenems restores the activity against multidrug-resistant Gram-negative bacteria. The aim of this study was to summarize the evidence on the efficacy and safety of novel carbapenem–β-lactamase inhibitor combinations. Methods We conducted a meta-analysis of clinical trials comparing novel carbapenem–β-lactamase inhibitor combinations with comparators to assess the clinical and microbiological responses, mortality, and adverse events (AEs). Results A total of 1,984 patients were included. The pooled risk ratios (RRs) of clinical cure, microbiological eradication, all-cause mortality, and 28-day mortality were 1.11 (95% CI: 0.98–1.26), 0.98 (95% CI: 0.82–1.16), 0.90 (95% CI: 0.49–0.94), and 0.68 (95% CI: 0.49–0.94) between the novel carbapenem–β-lactamase inhibitor combinations and control groups. Sensitivity analysis revealed that the phase II trial of imipenem–cilastatin/relebactam (ICR) against complicated urinary tract infections could be the most important factor of heterogeneity for the microbiological response. The therapeutic effect of novel carbapenem–β-lactamase inhibitor combinations was better in meropenem–vaborbactam (MEV), phase III trials, and number of patients less than 200. The RRs of AEs from any cause and serious adverse events (SAEs) for patients receiving novel carbapenem–β-lactamase inhibitor combinations were 0.98 (95% CI: 0.93–1.04) and 1.01 (95% CI: 0.75–1.36), respectively. Conclusions ICR and MEV were superior to comparators for clinical cure and survival rate in the treatment of complicated infections, and both were as tolerable as the comparators.